2021
DOI: 10.24920/003866
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of Hyperlipidemia with the 28-Day All-Cause Mortality of COVID-19 in Hospitalized Patients

Wu Bin,
Zhou Jianghua,
Wang Wenxin
et al.

Abstract: Objective This study aimed to determine the association of hyperlipidemia with clinical endpoints among hospitalized patients with COVID-19, especially those with pre-existing cardiovascular diseases (CVDs) and diabetes. Methods This multicenter retrospective cohort study included all patients who were hospitalized due to COVID-19 from 21 hospitals in Hubei Province, China between December 31, 2019 and April 21, 2020. Patients who were aged < 18 or ≥ 85, in pregnancy, with acute lethal organ injury (e.g., acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…While previous studies found that hyperlipidemia is not significantly associated with all-cause mortality in COVID-19 patients, it in combination with COVID-19 may specifically predispose patients to hemorrhagic stroke. 21 Second, in contrast with previous studies, we did not find hemorrhagic stroke to be more common in patients with pre-existing hypertension and diabetes mellitus prior to COVID-19 infection. 22 Third, in the COVID-first cohort (N=45), the use of heparin prior to the stroke event showed no significant correlation with mortality (p=1.000) or type of stroke (p=0.321).…”
Section: Discussioncontrasting
confidence: 99%
“…While previous studies found that hyperlipidemia is not significantly associated with all-cause mortality in COVID-19 patients, it in combination with COVID-19 may specifically predispose patients to hemorrhagic stroke. 21 Second, in contrast with previous studies, we did not find hemorrhagic stroke to be more common in patients with pre-existing hypertension and diabetes mellitus prior to COVID-19 infection. 22 Third, in the COVID-first cohort (N=45), the use of heparin prior to the stroke event showed no significant correlation with mortality (p=1.000) or type of stroke (p=0.321).…”
Section: Discussioncontrasting
confidence: 99%
“…Thirty-four papers were reviewed after screening, which reported the incidence of hyperlipidemia in COVID-19 patients ( Table 2 ). 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 The incidence of hyperlipidemia ranged from 0.30% to 81.82% in COVID-19 patients among different studies. Potential reasons for the variations could be: 1) Regional factors led to the difference in baseline lipids levels; 2) The definition of hyperlipidemia varied in different studies.…”
Section: The Correlation Between Hyperlipidemia and Covid-19mentioning
confidence: 99%
“…However, another study analyzing the association of hyperlipidemia with overall mortality within 28 days of COVID-19 in hospitalized patients did not show evidence that an unbalanced lipid profile would be significantly associated with allcause mortality, even in patients with cardiovascular diseases (CVDs) and previous diabetes mellitus. Therefore, hyperlipidemia would not be the main risk factor for the severity of COVID-19, but a contributing factor for worse outcomes (Wu et al, 2021).…”
Section: Dyslipidemias and Covid-19mentioning
confidence: 99%